Ensiling Additives for better preservation of forages during lean seasons - Sridhar, Manpal; Elangovan, A V; Senani3, S; Samanta, A K; Gorti, R K; G, Maya (Indian Farming, 2020)
It is highly essential to ensile forages to produce feed high in nutritive value and of sound microbiological quality in order to ensure the continuous superior animal health and growth during lean fodder periods. Apart from maize, most of the grasses and fodder crops require additives for good silage making. Silage additives can improve silage quality (by increasing nutritional content) as well as animal performance (body weight, milk production, reproduction). Silage forage in to good, but they definitely can help in making good quality forage into excellent quality silage. Silage additives can be beneficial and economical to use. Good results have been obtained with microbial inoculants, though results with enzyme additives have been inconsistent. Effects of microbial inoculants on aerobic stability are also not consistent. Anhydrous ammonia and propionic acid can improve the aerobic stability of silages, but their use is not widespread on account of handling problems and economics. To make good silage use of an additive is recommended, but caution should be exercised in choosing the right additive.